(untitled) - Sherman, Dennis (New York, 2012)
WEST illustrates the significance of economic, political, social and cultural interactions that shaped Western Civilization while asking students to analyze events and themes in order to build a greater understanding of the past and its influence and impact on the present. With WEST, students are no longer simply reading a static page. They are interacting and engaging in a visual and hands-on learning experience. As students experience the history of Western Civilization, WEST builds the critical analysis skills that will student success in this history course and beyond.
Keywords: Civilization, Western,Văn minh Phương Tây,Văn minh Phương Tây,Văn minh Phương Tây,Civilization, Western; History,Textbooks,Lịch sử,Nguồn,Lịch sử,Nguồn,Lịch sử,Sách giáo khoa,History,Sources